The Evolution of Food Assistance Programs in the United States - Nation, Madeleine (Colloquium: The Political Science Journal of Boston College, 2018)
Through an examination of public policy, legislative discussions, and statistical analysis of the Supplemental Nutrition Assistance Program (formerly the Food Stamps program), this paper concludes that agricultural and business interests have frequently taken precedent over hunger relief in American social policy formation. Agricultural and business interests first asserted strong control over the program in the 1930s and this uneven power dynamic has been continuously reinforced through various policy reforms over the decades. The auxiliary importance of hunger to social welfare programs in the United States is especially apparent through the written policy goals of the program, which place agricultural and business interests first and hunger relief second, but can also be seen through the structure of the program, the political rhetoric used to describe hunger relief, and the vulnerability of SNAP in times of economic distress. In order to undo the stronghold of exterior interests on hunger relief, Nation concludes that the United States should shift from an agricultural- and business-based approach to hunger to a rights-based approach to hunger.